Intermetallics evolution and its reliability effects on micro-joints in flip chip assemblies. Issue 3 (3rd February 2020) - Tian, Ye; Fang, Heng; Ren, Ning; Qiu, Chao; Chen, Fan; Sitaraman, Suresh
Abstract : Purpose: This paper aims to assess precise correlations between intermetallic compounds (IMCs) microstructure evolutions and the reliability of micro-joints with a Cu/SAC305solder/Ni structure using thermal shock (TS) tests. Design/methodology/approach: This paper uses 200- µ m pitch silicon flip chips with nickel (Ni) pads and stand-off height of approximately 60 µ m, assembled on substrates with copper (Cu) pads. After assembly, the samples were subjected to air-to-air thermal shock testing from 55 to 125 per cent. The transfer time was less than 5 s, and the dwell time at each temperature extreme was 15 min. To investigate the microstructure evolution and crack growth, two samples were removed from the thermal shock chamber at 0, 400, 1, 200, 2, 000, 5, 800 and 7, 000 cycles. Findings: The results showed that one (Cu, Ni)6 Sn5 /(Ni, Cu)3 Sn4 dual-layer structure formed at the Ni pad interface of chip side dominates the micro-joints failure. This is because substantial (Ni, Cu)3 Sn4 grain boundaries provide a preferential pathway for the catastrophic crack growth. Other IMCs microstructure evolutions that cause the prevalent joints failure as previously reported, i.e. thickened interfacial (Cu, Ni)6 Sn5 and Ni3 P layer, and coarsened IMCs inside the solder matrix, only contributed to the occurrence of fine cracks. Moreover, the typical interfacial IMCs spalling triggered by thermally induced stress did not take place in this study, showing a positive impact in the micro-joint reliability. Originality/value: As sustained trends toward multi-functionality and miniaturization of microelectronic devices, the joints size is required to be constantly scaled down in advanced packages. This arises a fact that the reliability of small-size joints is more sensitive to the IMCs because of their high volume proportion and greatly complicated microstructure evolutions. This paper evaluated precise correlations between IMCs microstructure evolutions and the reliability of micro-joints with a Cu/SAC305solder/Ni structure using TS tests. It found that one (Cu, Ni)6 Sn5 /(Ni, Cu)3 Sn4 dual-layer structure formed at the Ni pad interface dominate the micro-joints failure, whereas other IMCs microstructure evolutions that cause the prevalent joints failure exhibited nearly negligible effects.